Input current interharmonics in adjustable speed drives caused by fixed-frequency modulation techniques - Soltani, H.; Davari, P.; Loh, P.; Blaabjerg, F.; Zare, Firuz (2016)
© 2016 IEEE. Adjustable Speed Drives (ASDs) based on double-stage conversion systems may inject interharmonics distortion into the grid, other than the well-known characteristic harmonic components. The problems created by interharmonics make it necessary to find their precise sources, and, to adopt an appropriate strategy for minimizing their effects. This paper investigates the ASD s input current interharmonic sources caused by applying symmetrical regularly sampled fixed-frequency modulation techniques on the inverter. The interharmonics generation process is precisely formulated and comparative results of different fixed-frequency modulation techniques are presented to evaluate the drive input current interharmonic components. The theoretical analysis and simulation studies are validated with experimental results on a 2.2 kW motor drive system.